How practice makes sense in healthcare operations: Studying sensemaking as performative, material-discursive practice - Hultin, Lotta; Mähring, Magnus (Human relations (New York), 2017)
This article aims to move sensemaking theory forward by exploring a post-humanist view of how sense is made in material-discursive practices. Answering recent calls for novel theoretical views on sensemaking, we adopt a relational ontology, assuming subject and object to be ontologically entangled, and viewing agency as a circulating flow through material-discursive practices. Employing this perspective, we study how sensemaking unfolds at the emergency ward of a Nordic university hospital. By working through the concepts of material-discursive practices, flow of agency and subject positions, we produce an account of sensemaking that decenters the human actor as the locus and source of sensemaking, and foregrounds the performativity of practices through which certain ways of acting become enacted as sensible. This allows us to propose an alternative to the traditional view of sensemaking as episodic, cognitive-discursive practices enacted within and between separate human actors. With this view, what makes sense is understood as a material-discursive practice and related subject positions, which owing to their specific positioning in the circulating flow of agency emerge as sensible. Consequently, every actor is not just making sense, but is also already being made sense of; positioning and being positioned in the flow of agency.